Property as Governance: Time, Space and Belonging in Australia’s Northern Territory Intervention - Keenan, Sarah (Wiley, 2013)
This article analyses two cases brought by aboriginal Australians against the Australian government acquisition of long leases of their land under the Northern Territory National Emergency Response Act 2007. These leases are conspicuous, particularly in that the government always made it clear that it would not take up its right to exclusive possession of the leased land, and has not done so. The leases have not been used to evict residents, as some feared; nor to pursue mining or agricultural activity. Socio-legal theories centered on the right to exclusive possession cannot account for these leases. The article explores the use of property under the 2007 Act, the legal geographies of the areas subject to the leases and the political potency of property beyond exclusive possession, and suggests an understanding of property as a spatially contingent relation of belonging. Specifically, the article argues that property is productive of temporal and spatial order and so can function as a tool of governance.